Stercoral Colitis in a Patient With Pediatric-Onset Systemic Lupus Erythematosus: Case Analysis and Review of the Literature - Gau, Chun-Chun; Lin, Li-Lun; Wu, Chao-Yi; Huang, Jing-Long (Frontiers in Pediatrics, 2021)
Systemic lupus erythematosus (SLE) is an autoantibody-related disease that affects multiple organs. Stercoral colitis (SC) is a rare type of inflammatory colitis with a high mortality rate. Here, we report the first case of pediatric-onset lupus in a case complicated by stercoral colitis. We also conducted a literature review of patients with SC under 30 years old to provide useful clues for rapid diagnosis at a young age. A 28-year-old female with a history of lupus and neuropsychiatric SLE was admitted with severe abdominal pain. She was found to have stercoral colitis during surgery. Two years later, the patient underwent Hartman’s operation due to ischemia of the colon. In addition, 10 patients younger than 30 years old with a diagnosis of SC were analyzed based on clinical presentation, physical examination, laboratory exam, imaging and treatment. All cases had a favorable outcome without mortality. Stercoral colitis is a rare but lethal complication, emphasizing the importance of a multidisciplinary approach. Differential diagnosis should include stercoral colitis for patients with SLE developing unexplained sharp abdominal pain.